Structural, electrical transport and magnetic properties of Palladium (II) chloride added Bi1.6Pb0.4Sr2CaCu2O8 superconductor - Salma, M. A.; Ilhamsyah, A. B.P.; Abd-Shukor, R.; Mohd Hapipi, N.; Awang Kechik, M. M.; Lim, K. P.; Hak, R. Che; Baqiah, H.; Chen, S. K. (Springer, 2026)
In this study, the effect of palladium (II) chloride (PdCl2) addition on the structural, microstructural, and superconducting properties of Bi1.6Pb0.4Sr2CaCu2O8 (Bi-2212) was investigated. X-ray diffraction (XRD) confirmed Bi-2212 as the dominant phase in all samples. The incorporation of PdCl2 led to a reduction in both lattice parameters and unit cell volume. Scanning electron microscopy (SEM) revealed platy grains in PdCl2-added samples compared to the pure one. Both the onset transition temperature (Tc onset) and magnetic susceptibility transition temperature (Tcχ′) improved with PdCl2 addition. The 0.4 wt% PdCl2-added sample exhibited the highest Tc onset of 96 K and a zero-resistance transition temperature (Tc zero) of 77 K. AC susceptibility measurements showed that samples with x = 1.0 and 1.5 wt% PdCl2 exhibited the highest Tcχ′ of 86 K. The 0.4 wt% PdCl2-added sample also showed the highest intergrain loss peak temperature (Tp2), indicating enhanced flux pinning strength. PdCl2 addition influenced crystallite size, which contributed to the improved superconducting performance of Bi-2212 phase. These results demonstrated that the decreased crystallite size due to the PdCl2 addition may have induced defects that serve as effective flux pinning center of Bi-2212 superconductor.